Shaping Educational Experiences Through Language, Communication, and Identity - Paunanthie, A.; Tholappan, A. (Red’Shine Publication, Sweden, 2025)
In this chapter, the relationship between language, communication, and identity in education is explained. The paper contends that classrooms are not value-free contexts for the transmission of skills but rather are dynamic locations where student subjectivities are both negotiated and produced. This social validation, while it is employed, validates, privileges, and empowers a dominant “standard” language and class group, marginalizing others. Clearly, this power differential, which manifests through “knowledge” of one’s own linguistic superiority and hegemonic discourse in the classroom, can lead to student alienation, identity conflict, and reduced academic engagement. Instead, this chapter offers a possible direction for a pedagogy that is empowering and respects linguistic identity. It espouses all concepts related to translanguaging, using the full language capability of students as well as Culturally Sustaining Pedagogy, culturally and linguistically sustaining practices in the CLR classroom. From this process of developing a critical language awareness and training instructors, classrooms can be transformed to be accommodating of and respectful to linguistic diversity, seeing it as a strength for learning and as a foundation for liberation.
Keywords: Linguistic Identity; Translanguaging; Culturally Sustaining Pedagogy; Standard Language Ideology; Critical Language Awareness